2011
DOI: 10.2166/wst.2011.148
|View full text |Cite
|
Sign up to set email alerts
|

Characteristic of algogenic organic matter and its effect on UF membrane fouling

Abstract: Algogenic organic matter (AOM) was extracted from blue-green algae (cyanobacteria) and its characteristic was determined by various methods including high-pressure size-exclusion chromatography (HP-SEC), hydrophobic and hydrophilic fractionation, molecular weight (MW) fractionation and fluorescence excitation emission matrix (EEM). The results revealed that AOM was hydrophilic fractionation predominantly, accounting for 78%. The specific ultraviolet absorbance of AOM was 1.1 L/(mg m) only. The analysis for MW … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(11 citation statements)
references
References 8 publications
0
11
0
Order By: Relevance
“…The membrane filtration can remove more hydrophilic substances than hydrophobic substances. This indicated that the hydrophilic substances and proteins are main UF membrane fouling contributors (Li et al, ). And the inline coagulation can remove more organics than direct UF.…”
Section: Resultsmentioning
confidence: 99%
“…The membrane filtration can remove more hydrophilic substances than hydrophobic substances. This indicated that the hydrophilic substances and proteins are main UF membrane fouling contributors (Li et al, ). And the inline coagulation can remove more organics than direct UF.…”
Section: Resultsmentioning
confidence: 99%
“…The mobile phase solution was made with 0.05 M KH 2 PO 4 , and 0.03 M NaOH. Polyethylene glycols (PEGs) and sodium polystyrene sulfonates (PSSs) (PEGs: 200, 1400 Da; PSS: 3610, 6800, 15450, 31000 Da) were used as standards for calibration (Li et al, 2011). A simultaneous determination method, combining solidphase extraction (SPE) enrichment, HPLC, and triple quadrupole MS (tqMS) with atmospheric pressure chemical ionization (APCI), using selective reaction monitoring (SRM) in the positive mode, was developed in a previous study (Chu et al, 2012a) and applied in the current study.…”
Section: Analyzingmentioning
confidence: 99%
“…As UF can effectively remove algal cells without destroying them, it has a great potential for algae-rich water treatment [10]. However, the deposition of algal cells and extracellular organic matter (EOM) on the membrane can cause severe membrane fouling, especially for EOM which is a typical type of autochthonous natural organic matter (NOM) [11,12]. Henderson et al extracted and characterized the EOM from cyanobacteria, green algae and diatoms, and found that the EOM was comprised of proteins, polysaccharides and humic-like substances [13].…”
Section: Introductionmentioning
confidence: 99%